Costimulation blockade in pig artery patch xenotransplantation - a simple model to monitor the adaptive immune response in nonhuman primates. (2012)
BACKGROUND: CD154 blockade-based immunosuppression successfully prevents both humoral and cellular adaptive immune responses in baboons receiving α1,3-galactosyltransferase gene-knockout (GTKO) pig organs. Using a GTKO pig artery transplantation model in baboons, we evaluated the efficacy of CD28/B7 costimulatory pathway blockade in comparison with CD154 blockade.